Malnutrition and Cachexia in Heart Failure. (29th January 2015) - Rahman, Adam; Jafry, Syed; Jeejeebhoy, Khursheed; Nagpal, A. Dave; Pisani, Barbara; Agarwala, Ravi
Abstract : Heart failure is a growing public health concern. Advanced heart failure is frequently associated with severe muscle wasting, termed cardiac cachexia . This process is driven by systemic inflammation and tumor necrosis factor in a manner common to other forms of disease‐related wasting seen with cancer or human immunodeficiency virus. A variable degree of malnutrition is often superimposed from poor nutrient intake. Cardiac cachexia significantly decreases quality of life and survival in patients with heart failure. This review outlines the evaluation of nutrition status in heart failure, explores the pathophysiology of cardiac cachexia, and discusses therapeutic interventions targeting wasting in these patients.